Evaluations of Nursing Students’ Knowledge of Peripheral Veins Catheter Care - Janiušina, Diana; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2020)
The aim of the study.  To evaluate nursing students' knowledge of peripheral vein catheter care.Methods. Quantitative research was conducted at LSMU Faculty of Nursing in January – February, 2020. Second and fourth year nursing students (n = 160) of the first study cycle of the Faculty of Nursing participated in the study. A questionnaire was made by the study authors. LSMU Bioethical approval for study No. BEC-1L (B) -50 was obtained.Results. The majority of second- and fourth-year nursing students (respectively, 72.4% and 81.3%) correctly indicated that the longest peripheral venous catheter inserted could be stored for 72 hours. Second and fourth year students knew best (respectively, 94.8% and 97.9 %,) that medical diagnostic gloves should be worn when inserting a peripheral venous catheter, but 3.4% of second year students did. Students replied that gloves were not required. The majority of second- and fourth-year nursing students (respectively, 63.8% and 72.9 %,) correctly answered that a transparent polyurethane bandage is best suited for peripheral venous catheter fixation. Nursing students were aware of documenting the date of insertion (98.1%), flushing the catheter (92.5%), and documenting the time of insertion (90.6%) during peripheral venous catheter maintenance. Nursing students were least aware of the documentation of the site of administration (71.7%), the application of retelast bandage or other material (73.6%). However, second-year students were better aware of the application of retelast bandage or other material than fouth-year students (81.0% and 73.6%, respectively). All (100%) nursing students correctly answered that the peripheral venous catheter insertion site should be inspected and evaluated when a patient complains of pain at the peripheral catheter site. Fourth-year students were more likely (93.8%) to know that the bandage used to fix the peripheral venous catheter needed to be changed when the patient bathed with the bandage than second-year students in the nursing program (75.9%).Conclusions. The second and fourth year nursing students had sufficient knowledge of peripheral venous catheter care. Fourth year nursing students knew better about the duration of insertion of the inserted peripheral vein catheter, catheter fixation, use of medical diagnostic gloves when changing the bandage used to fix the peripheral vein catheter, but when the peripheral vein catheter was inspected, time of possible infection better knew second year students.
Keywords: peripheral vein catheter; nursing students; catheter care